Mischa elman favorite encores: A polio of sixteen compositions for violin and piano - ELMAN, Mischa (Carl Fischer, 1918)
Alben, 1 Tango, Amani, N Orientale, Beethooven Manuet No. 2 In G, L. Van, Cui Cesar Orientale (from Kaleidoscope) Op. 50, No.9